Regulatory T cells control toxicity in a humanized model of IL-2 therapy. Issue 1 (December 2017) - Li, Yan; Strick-Marchand, Helene; Lim, Ai Ing; Ren, Jiazi; Masse-Ranson, Guillemette; Li,; Jouvion, Gregory; Rogge, Lars; Lucas, Sophie; Li,; Di Santo, James
Abstract While patient selection and clinical management have reduced high-dose IL-2 (HDIL2) immunotherapy toxicities, the immune mechanisms that underlie HDIL2-induced morbidity remain unclear. Here we show that dose-dependent morbidity and mortality of IL-2 immunotherapy can be modeled in human immune system (HIS) mice. Depletion of human T cell subsets during the HDIL2 treatment reduces toxicity, pointing to the central function of T cells. Preferential expansion of effector T cells secondary to defective suppressive capacity of regulatory T (Treg ) cells after HDIL2 therapy further underscores the importance of Treg in the maintenance of immune tolerance. IL-2 toxicity is induced by selective depletion or inhibition of Treg after LDIL2 therapy, and is ameliorated in HDIL2-treated HIS mice receiving the PIM-1 kinase inhibitor, Kaempferol. Modeling IL-2 pathophysiology in HIS mice offers a means to understand the functions of effector and regulatory T cells in immune-mediated toxicities associated with cancer immunotherapy. High dose IL-2 is a viable treatment option for cancer immune therapy, but the underlying mechanism for the accompanying undesirable morbidity is unclear. Here the authors show, using human immune system mouse models, that regulatory T cells and their functions on effector T cells are essential modulators of the related pathogenesis.